ENERGY RELAXATION AT THZ FREQUENCIES IN ALXGA1-XAS HETEROSTRUCTURES - Asmar, N. G.; Markelz, A. G.; Gwinn, E. G.; Hopkins, P. F.; Gossard, A. C. (Semiconductor Science and Technology, 1994)
We report 4.2 K studies of the dependence of the in-plane, DC conductivity of a quasi 2D electron gas on the amplitude E(omega) of applied fields with frequencies from 0.25 THz to 3.5 THz. We analyse the dependence of sigma(DC) on E(omega) assuming that electron-optical phonon scattering dominates energy relaxation, that the absorbed power has a Drude form and that the electron distribution is thermal. This simple analysis is self-consistent: Arrhenius plots of the estimated energy loss rate have a slope near -homega(LO)BAR/k(B) for all frequencies, as expected for energy loss by optical phonon emission. We find that the effective energy relaxation time tau(epsilon) varies with the frequency of the applied field, from tau(epsilon) approximately 4 ps at 0.34 THz to tau(epsilon) approximately 0.3 ps at 3.45 THz. This may indicate a frequency-dependent form for the hot-phonon distribution.